Analisis Karakteristik Penggunaan Aplikasi Peer To Peer Lending Fintech dengan Model PCI - Syarifah Syarifah; Wing Wahyu Winarno; Hanson Prihantoro Putro (STMIK Budi Darma, 2020)
This study aims to determine the characteristics that influence the intention to use Peer to peer lending fintech applications with the Perceived Characteristics of Innovation (PCI) model. This study was conducted on 203 respondents who used the peer to peer lending fintech application and 114 respondents who did not use the Peer to peer lending fintech application in Indonesia. The results of this study indicate that the characteristics of innovation relative advantage, complexity, and observability can be determinants of people's intentions in using the Peer to peer lending application Fintech. Other characteristics of compatibility and trialability cannot be predictors of public interest in using peer to peer lending fintech services. There are other factors in people who do not use peer to peer lending fintech applications that most people are not interested in using applications. Some feel the application of peer to peer lending is against religion. Most of the other reasons are that they have never heard of the application and the public feels the complexity of using the peer to peer lending fintech application